The Debate Between Religious and Minangkabau Traditional Figures About Pagang Gadai (Pawn) Land in Agam Regency, West Sumatra, Indonesia - Willya, Evra; Idris, Muh; Wahid, Abdul (AHKAM : Jurnal Ilmu Syariah, 2024)
This research aims to analyze the debate between religious and traditional figures over pagang gadai land in Agam Regency, West Sumatra, Indonesia. This research is essential for religious figures to consider the practice of pawning that the community has carried out to be usury. It employed qualitative methods with a case research approach and used the maṣlaḥah mursalah theory to analyze the data. The primary data were obtained from informants, including religious leaders and members of the Indonesian Ulama Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah, as well as traditional figures comprising Kerapatan Adat Nagari (KAN) members. Some relevant books, literature, and journal articles were studied as secondary data. The study shows that the practice of pagang gadai is considered usury to religious figures but not traditional ones. Traditional figures view the practice of pagang gadai as belonging to bay’ al-wafā’, as it is a form of mutual assistance (ta’āwun) devoid of injustice but benefits both parties. The opinion of traditional figures on mutual assistance, based on the concept of benefit, is consistent with the maṣlaḥah mursalah theory that pagang gadai is valuable to society. Abstrak: Tujuan penelitian menganalisis perdebatan tokoh agama dan tokoh adat terkait pagang gadai tanah di Kabupaten Agam, Sumatera Barat, Indonesia. Penelitian ini penting untuk dilakukan karena praktek gadai yang selama ini dilakukan oleh masyarakat dianggap oleh para tokoh agama sebagai riba. Jenis penelitian kualitatif dengan pendekatan studi kasus dan teori maṣlaḥah mursalah digunakan untuk menganalisis data. Data primer diperoleh dari informan, yakni tokoh agama yang terdiri dari pimpinan dan anggota Majelis Ulama Indonesia (MUI), Nahdlatul Ulama (NU), dan Muhammadiyah, serta tokoh adat yang tergabung dalam Kerapatan Adat Nagari (KAN) sedangkan literatur buku dan artikel jurnal relevan dijadikan sumber sekunder. Hasil penelitian menunjukkan bahwa praktik pagang gadai dianggap riba oleh tokoh agama, namun tidak bagi tokoh adat. Tokoh adat memandang praktik pagang gadai termasuk dalam bay’ al-wafā’, karena merupakan bentuk gotong royong (ta’āwun) yang tidak mengandung unsur zalim namun menguntungkan kedua pihak yang mengambil manfaat darinya. Pendapat tokoh adat yang menitikberatkan pada konsep kemaslahatan, yakni tolong-menolong sejalan dengan teori maṣlaḥah mursalah bahwa pagang gadai dapat mewujudkan kemaslahatan di masyarakat.